Coeval Uplift and Subsidence Reveal Magma Recharging Near Rome (Italy). (13th May 2018) - Trasatti, E.; Marra, F.; Polcari, M.; Etiope, G.; Ciotoli, G.; Darrah, T. H.; Tedesco, D.; Stramondo, S.; Florindo, F.; Ventura, G.
Abstract: Uplift and subsidence alternate throughout the life cycle of a volcano mirroring magma accumulation, migration and/or gas pressurization, and magma cooling or depressurization, respectively. The unusual occurrence of coeval inflation and deflation is difficult to reconcile with the recharging or cooling of a single magma chamber, or hydrological processes. Here we show a persistent flank uplift and central subsidence at Colli Albani volcano near Rome (Italy), by mapping about 20 years of deformation by InSAR data. The magmatic helium signature increases in correspondence with N‐S faults along the western slope of Colli Albani, which are therefore interpreted as deep‐seated structures directly or indirectly connected with an underlying magma reservoir. Deformation modeling shows that these faults are pathways for fresh magma intrusion, whereas a residual magma is cooling below the deflating caldera. Therefore, magma recharge at depth is controlled by major faults along which the vents of the most recent activity (<200 ka ago) concentrate in the western side of the volcano and not by the caldera structures. We demonstrate that the Colli Albani magmatic system is slowly rejuvenating, posing a volcanic threat for Rome. Key Points: The Colli Albani volcano is characterized by lateral uplift and central subsidence Magmatic helium signature sharply increases in correspondence with N‐S faults on the western flank Deformation modeling suggests that the N‐S faults, not the caldera structures, control magma recharge at depth